CREG1 attenuates doxorubicin-induced cardiotoxicity by inhibiting the ferroptosis of cardiomyocytes - Dan Liu; Xiaoli Cheng; Hanlin Wu; Haixu Song; Yuxin Bu; Jing Wang; Xiaolin Zhang; Chenghui Yan; Yaling Han (Redox Biology, 2024)
Objective: Doxorubicin (DOX)-induced cardiotoxicity limits the application of DOX in cancer patients. Currently, there is no effective prevention or treatment for DOX-induced cardiotoxicity. The cellular repressor of E1A-stimulated genes (CREG1) is a cardioprotective factor that plays an important role in the maintenance of cardiomyocytes differentiation and homeostasis. However, the role and mechanism of CREG1 in DOX-induced cardiotoxicity has not yet been elucidated. Methods: In vivo, C57BL/6J mice, CREG1 transgenic and cardiac-specific CREG1 knockout mice were used to establish a DOX-induced cardiotoxicity model. H&E staining, Masson’s trichrome, WGA staining, real-time PCR, and western blotting were performed to examine fibrosis and ferroptosis in the myocardium. In vitro, neonatal mouse cardiomyocytes (NMCMs) were cultured and stimulated with DOX, CREG1-overexpressed adenovirus, and small interfering RNA was used to establish CREG1 overexpression or knockdown cardiomyocytes. Transcriptomics, real-time PCR, western blotting, and immunoprecipitation were used to examine the roles and mechanisms of CREG1 in cardiomyocytes ferroptosis. Results: The mRNA and protein levels of CREG1 were reduced in the hearts and NMCMs after DOX treatment. CREG1 overexpression alleviated myocardial damage and inhibited DOX-induced ferroptosis in the myocardium. CREG1 deficiency in the heart aggravated DOX-induced cardiotoxicity and ferroptosis. In vitro, CREG1 overexpression inhibited cardiomyocytes ferroptosis induced by DOX, and CREG1 knockdown aggravated DOX-induced cardiotoxicity. Mechanistically, CREG1 inhibited the mRNA and protein expression of pyruvate dehydrogenase kinase 4 (PDK4) by regulating the F-box and WD repeat domain containing 7 (FBXW7)-forkhead box O1 (FOXO1) pathway. PDK4 deficiency reversed the effects of CREG1 knockdown on cardiomyocytes ferroptosis following DOX treatment. Conclusion: CREG1 alleviated DOX-induced cardiotoxicity by inhibiting ferroptosis in cardiomyocytes. Our findings may help clarify the new roles of CREG1 in the development of DOX-induced cardiotoxicity.